Cloning, Sequencing, and Analysis of the Full-Length CDNA of Rhesus Monkey Factor IX - Ding, Y.; Wang, J.; Tan, W.; Chen, Younan; Lu, X.; Lu, Y.; Li, S.; Li, H.; Wang, L.; Cheng, J. (2008)
Objective: Coagulation factor IX (FIX) is a vitamin K-dependent serine protease, which plays a key role in the coagulation cascade. The rhesus monkey may be an indispensable substitute for humans in research of pig-to-human xenotransplantation, due to its close relationship. But the coagulation function concordance between rhesus monkey and human is unknown. In this study, we cloned the full-length cDNA of rhesus monkey FIX (rFIX) to investigate the genomic backgrounds of the coagulation systems. Method: We cloned the full-length cDNA from the cDNA library of rhesus monkey liver tissue. Polymerase chain reaction was used to screen the positive clones. Based on a partial sequence obtained by cDNA library screening and a homologous sequence from the database, we designed a second pair of primers to obtain the full sequence. For further analysis of rFIX, we used several online ExPASy Proteomic tools. Result: We obtained the full-length cDNA of rFIX, which has 2668 nucleotides, predicting an open reading frame of 1383 nucleotides corresponding to 461 amino acids. The deduced protein sequence indicated functional domains of signal peptide, Gla, two epidermal growth factor, and trypsin-like serine protease, which were consisted with those of human FIX (hFIX). Sequence alignments showed that rFIX is highly homologous to hFIX with nucleotide identity of 96% and amino acid identity of 97%. Conclusion: We have report herein the full-length cDNA of rFIX. The high homology between rhesus monkey and human coagulation factor ensure the reliability and feasibility of rhesus monkey as a recipient in studies on coagulation disorders in xenotransplantation. © 2008 Elsevier Inc. All rights reserved.